Three sibling species within Contracaecum osculatum (Nematoda, Ascaridida, Ascaridoidea) from the Atlantic Arctic-Boreal region: Reproductive isolation and host preferences - NASCETTI, Giuseppe; CIANCHI, Maria Rossella; MATTIUCCI, Simonetta; D'AMELIO, Stefano; PAGGI, Lia; BULLINI, Luciano; P. Orecchia; J. Brattey; B. Berland; J. W. Smith (International Journal for Parasitology, 1993)
Three sibling species within Contracaecum osculatum (Nematoda, Ascaridida, Ascaridoidea) from the Atlantic Arctic-Boreal region: reproductive isolation and host preferences. International Journal for Parasitology 23: 105-120. Genetic variation within and between population samples from 22 locations of the Atlantic Arctic-Boreal region, including 1657 specimens morphologically assigned to Contracaecum osculatum, was electrophoretically analysed at 17 loci. Highly significant deviations from the Hardy-Weinberg equilibrium were found at various loci in several samples, owing to the existence of three distinct gene pools within C. osculatum (sensu lato) from the study area. These gene pools correspond to three biological species (provisionally designated A, B and C), characterized by distinct genotypes at several diagnostic loci. Reproductive isolation between C osculatum A, B and C is confirmed by the lack of F1, recombinant, or backcross genotypes in sympatric areas, despite the occurrence of multiple infections. Mean heterozygosity per locus is on average 0.11 in species A, 0.10 in B and 0.07 in C. High levels of gene flow were found within each of the three species, the values of Nm (number of migrant individuals) ranging from 3.41 (C. osculatum C) to 5.77 (C. osculatum A). Average Nei's genetic distance is 0.46 between A and B, 0.50 between A and C and 0.77 between B and C. From these values, times of evolutionary divergence from 2 to 4 million years can be estimated. Genetic relationships among populations and species of the C. osculatum complex are illustrated by principal component analysis. The role of both geographical isolation and host preferences in the speciation of C. osculatum (sensu lato) is discussed. A morphological distinction of the three species has not yet been possible (sibling species). However, there is evidence that the name C. osculatum (sensu stricto) should be used for species C, which shows a geographical distribution and definitive host corresponding to the neotype of C. osculatum ...